Analisis Kesadaran Antikorupsi Mahasiswa Sosiologi dan Non-Sosiologi Terhadap Fenomena Pemungutan Parkir Ilegal di Indomaret - Elisa Diaz Agustina; Fransiscus Xaverius Sri Sadewo (Jurnal Adijaya Multidisplin, 2025)
The phenomenon of illegal levies by parking attendants at Indomaret is often found in every Indomaret stall. However, the collection of parking fees by parking attendants is an unlawful or illegal activity because Indomaret has paid sand levies to the city or district government. This form of collection is included in corruption. The purpose of this study was to determine the perceptions of sociology students and non-sociology students UNESA against the phenomenon of extortion in Indomaret and the form of awareness of anti-corruption behavior in sociology students and non-sociology students Unesa. This research is a qualitative study with literature and interview techniques which are then analyzed using structural analysis of functionalism. The results found that students who have had activities or courses on corruption can explain, and classify types of corruption better. In addition, based on functionalist structural analysis, it was found that the phenomenon of illegal levies at Indomaret is a form of dysfunction in the system, because it violates the rules and harms the community.